1991
DOI: 10.1002/j.1556-6978.1991.tb01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Predicate Usage and Communication Proficiency on Ratings of Counselor Empathic Understanding

Abstract: This study investigated the effect of predicate usage, facilitative skill level, and participant sex on the participants' ratings of empathic understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The microskills model of training provides the opportunity to practice listening attentively and responding empathically (Goldin & Doyle, 1991). Active listening is often lost because of concerns about performing other skills.…”
Section: Active Listeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The microskills model of training provides the opportunity to practice listening attentively and responding empathically (Goldin & Doyle, 1991). Active listening is often lost because of concerns about performing other skills.…”
Section: Active Listeningmentioning
confidence: 99%
“…cific words or counseling techniques used (Goldin & Doyle, 1991). The counselor-client working alliance, the relationships of two human beings in the room together, is the foundation upon which counseling is built (Meier & Davis, 1997;Egan, 1998).…”
mentioning
confidence: 99%
“…Craig, Peer, and Ross (1989) state that, “... [CRR] staff function typically as facilitators, mediators, advocates, consultants, and ‘helpers' ...” (p. 72). In order for the staff to function in each of these roles sufficiently, they need to be skilled (Craig et al, 1989; Goldin & Doyle, 1991; Marshal, 1989; Rogers, Cohen, Danley, Hutchison, & Anthony, 1986). Furthermore, it is necessary for staff to be able to adapt these roles to the needs of their clients.…”
Section: Community Residential Rehabilitation Programsmentioning
confidence: 99%
“…Goldin and Doyle (1991) conducted a study on communication effectiveness of counselors and found that an essential skill needed for efficient counseling is the capacity to show empathic understanding. It enhances the ability to convey to clients an accurate understanding and perception of what they communicate; furthermore, it fosters rapport.…”
Section: Community Residential Rehabilitation Programsmentioning
confidence: 99%